Isolation of Saccharomyces Cerevisiae and Production of Invertase Enzyme - Sheeraz Ahmed Khaskheli, Ahsan Abbas Abro, Syed Habib Ahmed Naqvi (International Journal of Modern Agriculture, 2021)
In the present study industrially important yeast Saccharomyces cerevisiae was isolated from grape samples using dilution and plating technique. The isolated Saccharomyces cerevisiae was tested for the invertase production by using different carbon and nitrogen sources at 37Â°C temperature and 5 pH. The maximum growth of saccharomyces cerevisiae was observed when sucrose (20g/L) was used as carbon source and peptone 20g/L as nitrogen source while the higher invertase production was observed at 48h. Total sugar, reducing sugar and total protein concentrations was also checked by using spectrophotometric method. Isolated Invertase (Î²-fructofuranosidase) could be utilized in food, cosmetics, and pharmaceutical industries.